Favorable outcomes of surgical resection for extrahepatic recurrent hepatocellular carcinoma. Issue 8 (23rd June 2020) - Midorikawa, Yutaka; Takayama, Tadatoshi; Nakayama, Hisashi; Moriguchi, Masamichi; Aramaki, Osamu; Yamazaki, Shintaro; Teramoto, Kenichi; Yoshida, Nao; Kobayashi, Naoya; Tsuji, Shingo; Higaki, Tokio
Abstract : Aim: Repeat resection for intrahepatic recurrent hepatocellular carcinoma (HCC) is effective for the long‐term survival of patients; however, little is known about the surgical outcomes of extrahepatic nodules. The aim of this study is to investigate whether resection can contribute to the survival of patients with extrahepatic recurrent HCC. Methods: Under the conditions that intrahepatic recurrent HCC was absent or controlled by locoregional therapies, patients who had resectable extrahepatic recurrent HCC in the lymph nodes, adrenal gland, peritoneum, lung, or brain were included in this study. The survival of patients who did (Surgical group) and did not (Non‐surgical group, underwent other therapies) undergo resection for extrahepatic recurrent HCC was compared. Results: Thirty‐eight and 26 patients were included in the Surgical and Non‐surgical groups, respectively. No patient had severe postoperative complications. After a median follow‐up of 1.2 (range, 0.2–8.8) years, the median cumulative incidence of extrahepatic recurrent HCC was 1.2 years (95% confidence interval [CI], 0.4–3.5) in the Surgical group. The median overall survival was 5.3 (95% CI, 2.5–8.8) and 1.1 (0.8–2.3) years in the Surgical and Non‐surgical groups, respectively ( P  < 0.001). The 5‐year rates of survival were 60.5% and 9.1% in the Surgical and Non‐surgical groups, respectively. Surgical resection, α‐fetoprotein, disease‐free interval, and metastasis at the adrenal gland were the independent factors for overall survival. Conclusions: Due to the favorable surgical outcomes, resection should be considered as one of the therapeutic choices for patients with extrahepatic recurrent HCC if intrahepatic recurrent HCC can be controlled by locoregional therapies.